PO 8171 Predictors of loss to follow-up in ART-commenced patients in nigeria: a 13-year review (2004–2017). (24th April 2019) - Aliyu, Ahmad; Adelekan, Babatunde; Andrew, Nifarta; Ekong, Eunice; Dapiap, Stephen; Murtala-Ibrahim, Fati; Ndembi, Nicaise; Nta, Iboro; Mensah, Charles; Dakum, Patrick
Abstract : Background: Expanded access to antiretroviral therapy (ART) has improved HIV outcomes in Nigeria. However, increasing rates of patients lost to follow-up (LTFU) is threatening the achievement of the UNAIDS treatment targets to treat 90% of HIV-diagnosed patients and attain 90% viral suppression amongst those on treatment. Therefore, this retrospective cross-sectional study is aimed at identifying correlates and predictors of loss to follow-up in ART-commenced patients in a large HIV programme in Nigeria. Methods: Records of all patients who started ART from 2004 to 2017 of 432 PEPFAR-supported facilities across 10 states in Nigeria were used for this study. Univariate, bivariate and multivariate analysis using frequencies, percentages, chi-square and logistic regression was conducted using STATA version 14 to determine occurrence, correlates and predictors of LTFU. Results: Among all 2 45 257 ever-enrolled-on-ART patients within the review period, 1 50 191 patients (61.2%) remained on treatment while 75 041 (30.6%) were LTFU. Patients were significantly more likely to be LTFU when non-pregnant female (OR: 4.55, p<0.001); on ≥3 monthly ARV refills (OR: 1.32, p<0.001); with unsuppressed viral loads on ART (OR: 4.52, p<0.001); adult on second-line regimen (OR: 1.23 p<0.001); paediatric on first-line regimen (OR: 1.70, p<0.001); 10–14 years (OR: 2.99, p<0.001); and ≥65 years (OR: 1622.84, p<0.001). Conclusion: Despite increasing access to ART, LTFU is still a challenge in the HIV programme in Nigeria with gender, type of regimen, age, unsuppressed viral load, duration of ARV refill, and duration of ART amongst others as significant predictors of LTFU. Differentiated care is advocated to prevent LTFU and improve retention of people living with HIV on treatment while further research to unravel the gender and social dimensions of LTFU is encouraged.